Effects of 5 antibrowning agents on the color parameters of Dangshan pear (Pyrus spp.) wine during storage. Issue 5 (18th April 2022) - Yang, Hua; Chen, Xuexue; Li, Xiaomin; Wu, Dianhui; Cai, Guolin; Lu, Jian
Abstract: The effects of ascorbic acid (VC), reduced glutathione (GSH), sulfur dioxide (SO2 ), chitosan, and ethylenediaminetetraacetic acid disodium (EDTA‐2Na) on the color parameters of Dangshan pear wine during storage were investigated. The different addition amounts of VC and EDTA‐2Na increased the browning degree of pear wine, and chitosan had a weak inhibitory effect on the browning of pear wine. The addition of 0.01%, 0.05%, and 0.10% GSH reduced the browning degree of pear wine by 8.80%, 13.82%, and 5.02%, respectively; 0.05% GSH decreased the color saturation and increased the brightness during the storage of pear wine. Adding 0.05% and 0.10% SO2 reduced the browning degree of pear wine by 14.73% and 21.05%, respectively, the inhibitory effect for browning was significant, 0.10% SO2 reduced the brightness of pear wine during storage. This result showed that GSH and SO2 were the most effective candidate inhibitors for Dangshan pear wine browning. Novelty impact statement: The addition of 0.05% GSH reduced the browning degree of pear wine by 13.82%. Adding 0.10% SO2 reduced the browning degree of pear wine by 21.05%. GSH and SO2 were the most effective inhibitors for Dangshan pear wine browning.